Quality Preschools: Commonalities and Uniqueness across Nations - Pupala, Branislav (Universitas Negeri Semarang, 2016)
This paper explores how different forms of pre-school education have developed in various countries on different continents. Particular attention is paid to European traditions of pre-school education and how their roots differ in post-communist countries and in traditional western European countries. It is drawn primarily from experience of one particular post-communist country Ã¢â‚¬â€œ the Slovak Republic. Doubt is cast on whether there is such a thing as a universal European tradition, and contrasts are made between Ã¢â‚¬Å“aestheticÃ¢â‚¬Â and Ã¢â‚¬Å“craftÃ¢â‚¬Â approaches to pre-school education. The paper highlights the historic roots of centralised national programmes that take the form of prescriptive documents concerned either with the inputs or outputs of education and which differ from a traditional, open, framework-based curriculum. It draws attention to the issue of a Ã¢â‚¬Å“culturally relevant pedagogyÃ¢â‚¬Â in the search for appropriate pre-schooling models for developing countries. The paper is based on the authorÃ¢â‚¬â„¢s personal experiences as the head of a team tasked with creating and implementing a new pre-school education programme in the Slovak Republic and as an academic performing comparative research on pre-school education in different cultures.